การวิเคราะห์พาราเบนในเครื่องสำอางโดยการสกัดระดับจุลภาคด้วยวัฏภาคของแข็งร่วมกับเทคนิคไฮเพอร์ฟอร์แมนซ์ลิควิดโครมาโทกราฟี - ฐิติมา วงษ์จำปี (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
Parabens are widely used as preservatives in cosmetic products in order to prevent the growth of mold and bacteria. However, excessive usage can affect consumer’s health. Therefore, this work developed a method for determining 4 parabens which are methyl paraben, ethyl paraben, propyl paraben and butyl paraben in a commercial cosmetic product by using solid phase microextraction (SPME) combined with high performance liquid chromatography (HPLC). As a result, direct immersion solid phase microextraction (DI-SPME) exhibited higher extraction of parabens compared with headspace solid phase microextraction (HS-SPME). Therefore, the condition in DI-SPME was optimized to improve the extraction efficiency. The optimal condition was extraction temperature of 50 °C, extraction time of 30 minutes, methanol as desorption solvent, desorption time of 30 minutes. Moreover, body lotion sample was pretreated by diluting with methanol, then vortexed and centrifuged before extracted by DI-SPME. The developed method showed good extraction efficiency with the recovery range of 68–115%.